Prinsip Transendental dalam Seni Visual Islam - Muhammad Budi Santoso; Mohammad Syam'un Salim (Tasfiyah: Jurnal Pemikiran Islam, 2018)
This paper tries to explain the principles of visual art in Islam. It is because study of art in Islam is almost forgetten. Furthermore, there are several people who declare that Islam goes against art and does not accept it. Whereas, the fact is not so. This research has revealed that Islam greatly appreciates art. Even more, ethics and aesthetics are discussed interestingly in the Islamic civilization. This is proved by availibility of transcendental principles in Islamic visual arts. Therefore, this paper is written to focus on arts including Islamic art definition and how the transcendental principles are reflected in Islamic visual art.